Problematyka etyczna w pierwszych dziełach o rachunkowości - Garstka, Małgorzata (Annales. Etyka w Życiu Gospodarczym, 2015)
Accountants recently had the opportunity to celebrate 20 years of existence in Poland the regulating of accounting. The act was adopted by parliament in 1994. 500 years before the treaty about double accounting was reprinted by Pacioli. The edition of Tractatus XI. Particularis de computis et scripturis was an (epic) epoch-making event designating the beginning of a new field of economic sciences. The idea of the double accounting was known before, not only because of Pacioli, but also through Cotruglio, who described it 36 years earlier. Recently in accounting, as well as in the broadly understood economy, there is a particular emphasis put on ethics, moral values and professional attitudes. It is worth considering whether and on what scale they were present in the early works of Accountancy 550 years ago, how their representatives approached the subjects the beginning of a written history of accounting. The article presents the main ideas included in the guidelines Pacioli and Cotruglio regarding double accounting, and identifies if ethical guidelines were presents among others guidelines. It turns out that the author of the essential work in the history of accounting, as well as its predecessor, devoted much attention to the moral attitude of the merchant, his appropriate behavior, attitude towards customers and other people, with whom he has a business relationship.